The Need for Communication Skills Training in Oncology - Hilaire, Dany Michaella (Harborside Press, 2013)
Communication between health-care professionals and their patients is an element that can make all the difference in how those patients navigate their cancer journey. In a 2011 issue of the Annals of Oncology, Barth and Lannen reported on their systematic review and meta-analysis of the efficacy of communication skills training courses in oncology. In this issue of JADPRO, two authors share their perspectives on the findings of Barth and Lannen and what advanced practitioners (APs) can learn from their research.